Analisis Pergeseran Sektor Ekonomi Kota Tarakan - Jabarsyah, Abdul (Ekonomika, 2010)
The purpose of this research to determine which economic sectors are experiencing a shift in economic structure. Followed by studying and formulating the base sector and non base in the city of Tarakan Period 2002-2007. Then find out where the economic sectors that experienced rapid growth and have strong competitiveness in The City Of Tarakan Period 2002-2007. Analysis tool used is the Shift Share Analysis and analysis of Location Quotient (LQ). Based on the analysis, sector of electricity, gas and watersupply, service sector, construction sector, transportation and communications sector,the agricultural sector, and construction sector because it has a value of more than one LQ (LQ>1). While mining and quarrying sector , as well as the manufacturing industry is the non-base in Tarakan City because it has a smaller RI values than one (LQ<1).Â Key Words: Economic Structure Shift, Sector Base, Non Base